Co-afflicted but invisible: A qualitative study of perceptions among informal caregivers in cancer care. (September 2021) - Tranberg, Mattias; Andersson, Magdalena; Nilbert, Mef; Rasmussen, Birgit H
This article explores the lived experience of informal caregivers in cancer care, focusing on the perceived burden and needs of individuals seeking support from an informal group for next of kin. A total of 28 individuals who were closely related to a patient with cancer participated in focus group interviews. Three themes were identified: setting aside one's own needs, assuming the role of project manager, and losing one's sense of identity. Together they form the framing theme: being co-afflicted. The characteristics of informal caregivers are shown to be similar to those of people with codependency, motivating development of targeted interventions from this perspective.